Asuhan Keperawatan Keluarga pada Keluarga dengan Hipertensi Di Wilayah Kerja Puskesmas Naras Tahun 2026 - Bunga Alia Lestari; Armaita Armaita; Prima Yoselina; Ramaita Ramaita (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Hypertension is one of the non-communicable diseases that commonly occurs in Indonesia and contributes to increased morbidity and mortality rates. Hypertension is often referred to as a silent killer because many sufferers are unaware of their condition until complications such as stroke, heart disease, and kidney failure occur. Based on data from the Naras Community Health Center, hypertension ranked second among the ten most common diseases, with 1,363 cases reported in 2025. This condition indicates that hypertension remains a health problem requiring special attention. This study aimed to implement family nursing care for families with hypertension in the working area of the Naras Community Health Center in 2026. The research method used was a case study with a family nursing process approach, including assessment, nursing diagnosis, intervention, implementation, and evaluation. Based on the results of the study conducted by the researcher from February 28 to March 6, 2026, in the working area of the Naras Community Health Center on Mrs. S’s family, it was found that the family lacked understanding regarding hypertension, its causes, signs and symptoms, home care, and the importance of routine blood pressure monitoring. The nursing problems identified were risk-prone behavior, noncompliance, and pain. The interventions provided included health education, recommendations for a low-salt diet, regular physical activity, medication adherence, and utilization of health services. After the nursing interventions were implemented, the family showed increased knowledge, was able to care for family members with hypertension, became more compliant with health check-ups, and experienced reduced pain complaints. It can be concluded that family nursing care is effective in helping control hypertension and prevent complications.